Moral Reciprocity, Ethics of Appropriation of Indigenous Medicinal Plant Knowledge and Associated Biopiracy - Ambang Oscar Agbor; Alloggio Sergio; Tandlich Roman (Sciendo, 2019)
Introduction: Although this paper deals mostly with the positive effects of a posthumanist worldview on environmental sustainability, partnership, or moral accountability in science and scientific research, it also promotes a new understanding of our educational practice in higher education. The ideas espoused have the ability to inspire educators at all levels to show students, future researchers or other professions about the importance of a progressive, holistic approach to our environment. We claim that being sensitive and caring for our environment is not only part of our moral and ethical responsibility, it is an inseparable aspect of our environmental education, our environmental intelligence. This paper discusses posthumanist1 reciprocity ethics in the context of traditional knowledge (TK) and the protection of indigenous traditional knowledge from commercial exploitation.